Religion and Diversity: Fifth Annual Conference 2022 - Cadeddu, Francesca (European Academy of Religion (EuARe) Lectures, 2024)
Diversity characterises internal dynamics and external relations of all religious groups. The four lectures offer insights into the role of religious education for today’s European society the challenges faced by academia in understanding change in religion the chances that religions may offer in supporting agency and resilience for refugees